1990
DOI: 10.1021/ed067p954
|View full text |Cite
|
Sign up to set email alerts
|

A supplemental course to improve performance in introductory chemistry

Abstract: The supplemental course presents a unique opportunity to teach effective methods for learning chemistry, to help students learn to think the way chemists think about their subject matter, and to apply these methods immediately to the subject matter of the parent course; includes format, objectives, approach, content, assignments, and results of the course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
2
Order By: Relevance
“…Studies have shown that students who have the ability to visualize chemical phenomena at the molecular level develop good conceptual understanding (7)(8)(9). Turner (10) notes that many students who don't succeed in chemistry courses "have never learned to visualize chemical systems or to make drawings to help solve problems". Computer technology not only allows the modeling of how experts think microscopically but also allows the simultaneous representation of microscopic and macroscopic views of the same phenomena.…”
Section: Design Rationalementioning
confidence: 99%
“…Studies have shown that students who have the ability to visualize chemical phenomena at the molecular level develop good conceptual understanding (7)(8)(9). Turner (10) notes that many students who don't succeed in chemistry courses "have never learned to visualize chemical systems or to make drawings to help solve problems". Computer technology not only allows the modeling of how experts think microscopically but also allows the simultaneous representation of microscopic and macroscopic views of the same phenomena.…”
Section: Design Rationalementioning
confidence: 99%
“…[22][23][24][25][26] Por meio da utilização desses instrumentos didáticos, é possível proporcionar uma aprendizagem mais eficiente e interessante para os alunos.…”
Section: Uso De Imagens No Ensino De Químicaunclassified
“…Many students feel they have a better understanding after practicing on old test problems. As pointed out by Turner (1), the presence of students who earn A and B grades in the workshop removes any perception of the workshop as remedial and helps integrate all workshop students into the chemistry course.…”
Section: The Workhopmentioning
confidence: 99%